Pretest Estimator for Individual Normal Means with Meta-analytic Data - Emura, Takeshi; Chang, Yuan-Tsung; Taketomi, Nanami; Konno, Yoshihiko; Mori, Mihoko (Journal of the Japan Statistical Society, Japanese Issue, 2025)
Meta-analysis is a statistical method to summarize quantitative results from a set of published studies. Meta-analysis often assumes that the outcomes of all individual studies have a common mean and estimates the common mean based on the results of each study. On the other hand, meta-analysis sometimes shows an updated estimate of individual study. This paper is a review article for estimation of individual normal means based on pretest estimators using meta-analytic data. New results on the bias, mean squared error, and variance of the pretest estimator are also included in this paper. The use of the R package: meta.shrinkage is also described. An example of the application to eye allergic reaction data during anatomy practice is also reported.